USE OF COGNITIVE TECHNOLOGIES IN THE EDUCATIONAL PROCESS (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
In this article, cognitive technologies, the use of cognitive technologies in teaching activities. An opinion was expressed about the professional training of future teachers and the development of their personal abilities.